Uso de recursos em saúde e custos em pacientes com artrite reumatoide em tratamento com terapia biológica no SUS - Buffon, Poliane Barbosa Sampaio (2021)
Introduction: This research was motivated by the need to analyze the trajectory of patients facing the introduction of new effective therapies for the treatment of Rheumatoid Arthritis (RA). Treatment with conventional synthetic disease-modifying drugs (csDMARD) and biological DMARD (bDMARD) for RA are provided by the Unified Health System (SUS). Available biological medicines are said to be expensive. Assessing the economic costs associated with AR is an action of great importance for decision making. The thesis was divided into three parts, the first part being a pharmacoepidemiological analysis, through secondary data, with a temporal trend, the profile of patients diagnosed with RA undergoing treatment with biological therapy treated at the Citizens' Pharmacies in Espírito Santo; the second part presents the results of a qualitative study that shows the paths taken through an individual experience of patients diagnosed with RA undergoing treatment with biological therapy and; the third part covers an analysis that portrays the use of resources and the valuation of these resources by patients diagnosed with RA from the perspective of the SUS. Objective: To assess the epidemiological characteristics of the use of health resources and costs under the broad perspective of the SUS by mapping the trajectory of all patients with rheumatoid arthritis treated with biological therapies in the state of Espírito Santo. Methodology: Retrospective cohort of secondary data in historical series, in order to analyze the profile, time series and estimate the use of health resources and costs by mapping the trajectory of all RA patients treated with biological therapies in ten public pharmacies, called Citizen Pharmacies, distributed in the municipalities of the state of Espírito Santo, served between 2009 and 2017. The record linkage technique was adopted in the joint use of the database of citizen pharmacies in ES between the Outpatient Production Bulletin (BPAB) and the System of Hospital Information (SIH) and High Complexity Procedure Authorization (APAC). A sensitivity analysis was carried out on the PMVG and PF prices of each drug used for RA provided by the SUS, through the change of key variables within the model, in order to understand different scenarios of expenses and trading values. A study with a qualitative approach was also carried out, carried out with ten subjects with RA using biological therapy, registered in a Citizen's Pharmacy. The material was produced through an open interview, in which, after transcription, the data were analyzed using the Content Analysis technique, in the Thematic Analysis modality. Two categories suggest, namely, Limits of Therapeutic Itineraries – which measure financial expenses, absence from work and the trajectory of treatment diagnosis; and Potentialities of Therapeutic Itineraries – knowledge about the treatment itself and access to SUS. Results: There were 9,804 requests for treatment with biological therapies, with dispensing concentrated in Citizen Pharmacies in the Metropolitan Region of the state (69%); with a predominance of women (84%), and mean age of 56 years; the drug with the highest prevalence was Adalimumab (40%), followed by Infliximab (21%), with a total expense of R$ 6,335,100.71. Of the 902 patients treated with RA using DMARDb, 783 were identified, after record linkage between 2009 and 2017. After the integration of the 3 databases BPAB, SIH and APAC, it was possible to match 386 (42.8%) patients. Of these, 83.9% were women, aged 56 12.2 years. During the period, 1147 outpatient and inpatient procedures were performed, 77.41% outpatients and 22.59% inpatients. When evaluating the average costs of these procedures (BPABR$96,556.08; SIH-R$765,644.00), it is observed that despite the SHI having a significantly lower number of procedures, its cost represents 88.80% of the resources used. The average cost per patient per year, with medicines (DMCDb + DMARDcs), considering the maximum, average and minimum scenarios was R$ 3,548,775.00, R$ 2,753,441.00 and R$ 2,090,033.00. The sum of all the average costs of all procedures was R$862,200.22 during the study period. Considering the estimated average scenario value for drugs, this means that biological therapy costs represent 94.27% of drug costs and 91.4% of all costs. In the study of therapeutic itineraries, family income was a significant issue of experiences, marking life stories, and told in their narratives; weaknesses in the early diagnosis were noticed, but the experiences lived during the process for the correct diagnosis and treatment provided the patients with an acquisition of knowledge about their disease. Conclusion: The linkage of SUS banks enabled the (re)construction of the trajectory of patients with RA on a large scale and the estimation of the use of resources and costs with the treatment of RA in Brazil. Spending on biological therapy is progressive and represents 91.4% of all costs. In the itinerary taken by the participants of this research, the delay in the diagnosis is noticeable and, with it, the worsening of the signs/or symptoms of the disease. None of the participants were diagnosed in less than a year of presenting the characteristics of the disease, regardless of being a total SUS patient or having a private health plan, and the difficulties in the itinerary were the same, that is, late diagnosis and impact on family income.